Preference for type of childbirth, factors associated with expectation and satisfaction with childbirth - Ana Carolina Lima Silva; Hévyllin Cipriano Rodrigues Félix; Maria Beatriz Guimarães Ferreira; Anneliese Domingues Wysocki; Divanice Contim; Mariana Torreglosa Ruiz (Universidade Federal de Goias, 2017)
This study aimed to analyze women's preference and satisfaction regarding the type of delivery and the association with the sociodemographic and obstetric characteristics. This is a cross-sectional study, carried out in three stages, with a sample of 190 puerperal women. The results showed that 68.9% wished natural childbirth and 31.1% wanted Cesarean section. The preference for natural childbirth was associated with first pregnancy (p=0.042) and previous natural childbirth experience (p<0.001); among women who had Cesarean section previously, the preference prevailed for Cesarean section (p<0.001). There were no statistical differences associated with other variables, as well as the puerperae's satisfaction. Binary logistic regression indicated association between previous experience and expectation by type of childbirth. The experience with previous childbirth influenced the preference for the type of childbirth; however, there were no differences in the puerperae's satisfaction, regardless of whether the outcome corresponded to the expectation.